2007
DOI: 10.1109/tvt.2007.906878
|View full text |Cite
|
Sign up to set email alerts
|

GSIS: A Secure and Privacy-Preserving Protocol for Vehicular Communications

Abstract: Abstract-In this paper, we first identify some unique design requirements in the aspects of security and privacy preservation for communications between different communication devices in Vehicular Ad Hoc Networks (VANETs). We then propose a novel secure and privacy preserving protocol based on Group Signature and Identity-based Signature techniques, called GSIS. We demonstrate that the proposed protocol can not only guarantee the requirements of security and privacy, but also provide desired traceability of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(84 citation statements)
references
References 24 publications
0
84
0
Order By: Relevance
“…Connected vehicles systems require efficient Vehicle-to-Vehicle (V2V) and Vehicle-to-Infrastructure (V2I) communication algorithms and appropriate driver responsiveness in order to avoid human errors that could lead to unsafe and congested traffic conditions. Computer scientists and engineers have focused on the security, safety and privacy of vehicular communications (Qianhong et al, 2010;Xiaodong et al, 2007) in connected environments. However, two critical questions regarding the traffic flow aspects need to be answered: (1) How to capture and specify the driving behaviors (tactical and operational) in a connected vehicle http://dx.doi.org/10.1016/j.trc.2015.07.007 0968-090X/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Connected vehicles systems require efficient Vehicle-to-Vehicle (V2V) and Vehicle-to-Infrastructure (V2I) communication algorithms and appropriate driver responsiveness in order to avoid human errors that could lead to unsafe and congested traffic conditions. Computer scientists and engineers have focused on the security, safety and privacy of vehicular communications (Qianhong et al, 2010;Xiaodong et al, 2007) in connected environments. However, two critical questions regarding the traffic flow aspects need to be answered: (1) How to capture and specify the driving behaviors (tactical and operational) in a connected vehicle http://dx.doi.org/10.1016/j.trc.2015.07.007 0968-090X/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Besides guarantee the needs of security and privacy, the proposed protocol provide the desired traceability of each vehicle whenever there is a dispute and the ID of the message sender has to be disclosed by the authority. In order to validate the competency of the proposed protocol in a range of application circumstances under different road systems, comprehensive simulation is conducted [3]. In order to overcome the problem on anonymous authentication for safety messages with authority traceability, this paper proposes an efficient conditional privacy preservation (ECPP) protocol in vehicular ad hoc networks (VANETs).…”
Section: Literature Surveymentioning
confidence: 99%
“…The public key and the Q-value are publicized. Steps (2)(3)(4)(5) are repeated by each node in the level-1. b) Encryption: Encryption: In the IOT environment let us assume E1 and E2 as two mobile subscriber.…”
Section: ) Pick a Random And Setmentioning
confidence: 99%
“…Many studies have been reported on the security and privacy-preservation issues for VANETs proposed by several authors (Raya and Hubaux, 2007;Lin et al, 2007;Zhang et al, 2008a;Ren et al, 2006;Lu et al, Science Publications JCS 2008). They can be grouped into three categories.…”
Section: Related Workmentioning
confidence: 99%